Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/gcbb.12878
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic interaction between biochar and nitrogen addition on soil greenhouse gas fluxes: A global synthesis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 95 publications
4
12
1
Order By: Relevance
“…Many reports indicate stimulation of N 2 O emission (T. He et al., 2018; Ji et al., 2020; L. Wang et al., 2020; Wu et al., 2021), while others confirm inhibition (Case et al., 2015; Y. He et al., 2021; Liao et al., 2021; Puga et al., 2020). BC often adsorbs NH 4 from soil, thereby reducing the pool of inorganic‐N for the N 2 O‐producing mechanisms (C. Li, Xiong, et al., 2021).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many reports indicate stimulation of N 2 O emission (T. He et al., 2018; Ji et al., 2020; L. Wang et al., 2020; Wu et al., 2021), while others confirm inhibition (Case et al., 2015; Y. He et al., 2021; Liao et al., 2021; Puga et al., 2020). BC often adsorbs NH 4 from soil, thereby reducing the pool of inorganic‐N for the N 2 O‐producing mechanisms (C. Li, Xiong, et al., 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Many reports indicate stimulation of N 2 O emission (T. He et al, 2018;Ji et al, 2020;L. Wang et al, 2020;Wu et al, 2021), while others confirm inhibition (Case et al, 2015;Y. He et al, 2021;Liao et al, 2021;Puga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A global biochar strategy has been projected to be capable of reducing as much as 12% of human CO 2 –C equivalent emissions annually (Woolf et al, 2010). Biochar is a carbon‐rich substance generated from biomass by the process of pyrolysis in the absence of oxygen (He et al, 2021). The physicochemical properties (e.g., composition, particle and pore size distribution) of the resulting biochar are largely controlled by pyrolysis conditions and feedstock characteristics, which determine its suitability for a given application, as well as its behavior, transport, and fate in the environment (Verheijen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies concluded that biochar application greatly reduces soil N 2 O emissions (Case et al, 2015; Han et al, 2021; Jia et al, 2012; Van Zwieten et al, 2014). The decrease in soil N 2 O emissions mostly resulted from improved soil aeration, pH modification, and N immobilization (He et al, 2021). In contrast, some other studies showed an enhancement in soil N 2 O levels after the addition of biochar (Bruun et al, 2011; Sánchez‐García et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation